ANALISIS PEMBIAYAAN UMKM MELALUI PROGRAM KREDIT USAHA TANI (KUT) DAN KREDIT USAHA RAKYAT (KUR) {Studi pada PT. BRI Manado (Persero)Tbk.} - , Drs. Dede Supriatna; , Drs Dumairy, MA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Micro, small and medium enterprises (MSMEs) is one of economic actors in national development, which has a strategic role where in 1997, the total reached 39.7 million units of SMEs, while in the year 2005 has reached 44.5 million. In terms of employment, in 2005, absorbed 77.68 million or 96.78 prosen of labor. Contribution to national GDP, about 54.22 prosen of GDP (2005) or in nominal value of Rp1480 trillion. However, in terms of its financing still low. The causes of the lack of accessibility of SMEs to financial institution (information, credit requirements, lack of credit collateral weak financial management of MSMEs), lack of capital, information technology, marketing, and production factors. Based on the above descriptions, the research aims to: 1) Examine the influence of the Local Economy Condition, Condition of SMEs and Government policies to the existence of KUT and KUR